The Rise of Apomixis in Natural Plant Populations - Hojsgaard, Diego; Hörandl, Elvira (Frontiers in Plant Science, 2019)
Apomixis, the asexual reproduction via seed, has many potential applications for plant breeding by maintaining desirable genotypes over generations. Since most major crops do not express natural apomixis, it is useful to understand the origin and maintenance of apomixis in natural plant systems. Here we review the state of knowledge on origin, establishment and maintenance of natural apomixis. Many studies suggest that hybridization, either on diploid or polyploid cytotypes, is a major trigger for the formation of unreduced female gametophytes, which represents the first step towards apomixis, and must be combined to parthenogenesis, the development of an unfertilized egg cell. Nevertheless, fertilization of endosperm is still needed for most apomictic plants. Coupling of these three steps appears to be a major constraint for shifts to natural apomixis. Adventitious embryony is another developmental pathway towards apomixis. Establishment of a newly arisen apomictic lineage is often fostered by side-effects of polyploidy. Polyploidy creates an immediate reproductive barrier against the diploid parental and progenitor populations; it can cause a breakdown of genetic self-incompatibility (SI) systems which is needed to establish self-fertility of pseudogamous apomictic lineages; and finally, polyploidy could indirectly help to establish an apomictic cytotype in a novel ecological niche by increasing adaptive potentials of the plants. This step may be followed by a phase of diversification and range expansion, mostly described as geographical parthenogenesis. The utilization of apomixis in crops must consider the potential risks of pollen transfer and introgression into sexual crop fields, which might be overcome by using pollen-sterile or cleistogamous variants. Another risk is the escape into natural vegetation and potential invasiveness of apomictic plants which needs careful management and consideration of ecological conditions.